Modeling of a System Dynamics of Fisherman Insurance Demand in Malang District - Lina Asmara Wati; Riski Agung Lestariadi; Supriyadi Supriyadi (Department of Aquaculture, 2021)
Fisherman Insurance Premium Assistance is applied to all coastal areas in Indonesia. In Malang Regency, it just started in 2016 through JASINDO, so many fishermen still do not fully understand the benefits against possible risks. Therefore, it is necessary to study the dynamics of the fisherman insurance system focusing on producing a model of insurance demand and the projection of the demand and growth of fisherman insurance in the future. The method used in this research was a series of system dynamics modeling. The results of the validity test in this study indicate the mean comparison and error variance is the following: fisherman insurance program = 4.8% and 6.01%; fishermen’s value = 4.0% and 21.55% and premium assistance = 3.9% and 12.17%. Moreover, the structural and parametric scenario analysis results show the average value of the increase in tourists: Scenario 1 - Structural: Premium assistance = 602 fishermen, Scenario 2 - Structural: 394 fishermen, Parametric Scenario 1 - Optimistic = 578 fishermen, Parametric Scenario 2 - Most Likely = 289 fishermen, and Parametric Scenario 3 - Pessimistic = 201 fishermen. However, the projection of the demand for fisherman insurance in 2021-2029 has not shown the expected results. The largest number of demands is 421 and the smallest is 321 in 2026. Moreover, after several simulations, the study found the most possible simulation to be carried out and to have a significant, stable effect on the results desired by the government, which is through premium assistance. If at least insurance premium assistance of Rp. 118,000x109 can be given annually, it will be able to generate a fisherman insurance demand at a minimum of 500.